2012
DOI: 10.1159/000339248
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome Incidence in a Large United States Cohort (2000–2009)

Abstract: Background/Aim: We describe the incidence of Guillain-Barré syndrome (GBS) in a large United States cohort. Methods: Between 2000 and 2009, we identified visits with an ICD-9 code for GBS (357.0) from all persons with continuous enrollment for at least 1 year. The primary case definition was restricted to emergency department and inpatient visits. We calculated age-standardized rates and used multivariate Poisson regression to assess variation in rates by sex, age, season and year of diagnosis. We tabulated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 56 publications
14
44
1
Order By: Relevance
“…Previous findings of increased risk in males as well as increasing risk with increasing age were also supported in our analyses [36]. The background incidence of GBS has also been shown to be about 40% higher in males than in females and to increase with increasing age [37].…”
Section: Discussionsupporting
confidence: 90%
“…Previous findings of increased risk in males as well as increasing risk with increasing age were also supported in our analyses [36]. The background incidence of GBS has also been shown to be about 40% higher in males than in females and to increase with increasing age [37].…”
Section: Discussionsupporting
confidence: 90%
“…High rates were reported for winter in cold regions and for spring in mild climate areas [30]. GBS incidence was 15% higher in winter and spring compared with summer in the United States [31], while no seasonal pattern of GBS was reported by Hughes and Rees [32]. Our multicenter study showed a seasonal trend with peaks in January and February 2011, possibly in relation to viral infection or vaccination.…”
Section: Discussionmentioning
confidence: 59%
“…Another report from the United States found increasing GBS incidence over the 10-year period [24] . In this study, the incidence rate increased gradually over the 15-year observational period ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Shui et al. reported results of a cohort study in the United States [24] and found that the GBS incidence rates estimated from emergency and in-patient visits were 15% higher in winter and spring than in summer and fall. Other studies documenting seasonal variation in GBS attributed this to higher rates of infection in certain seasons [7,12,18,25] .…”
Section: Discussionmentioning
confidence: 99%